Evaluation of the effects of adding vibrotactile feedback to myoelectric prosthesis users on performance and visual attention in a dual-task paradigm. (October 2018) - Raveh, Eitan; Friedman, Jason; Portnoy, Sigal
Objective: To evaluate the effects of adding vibrotactile feedback to myoelectric prosthesis users on the performance time and visual attention in a dual-task paradigm. Design: A repeated-measures design with a counterbalanced order of two conditions. Setting: Laboratory setting. Subjects: Transradial amputees using a myoelectric prosthesis with normal or corrected eyesight ( N  = 12, median age = 65 ± 13 years). Exclusion criteria were orthopedic or neurologic problems. Interventions: Subjects performed grasping tasks with their prosthesis, while controlling a virtual car on a road with their intact hand. The dual task was performed twice: with and without vibrotactile feedback. Main measures: Performance time of each of the grasping tasks and gaze behavior, measured by the number of times the subjects shifted their gaze toward their hand, the relative time they applied their attention to the screen, and percentage of error in the secondary task. Results: The mean performance time was significantly shorter ( P  = 0.024) when using vibrotactile feedback (93.2 ± 9.6 seconds) compared with the performance time measured when vibrotactile feedback was not available (107.8 ± 20.3 seconds). No significant differences were found between the two conditions in the number of times the gaze shifted from the screen to the hand, in the time the subjects applied their attention to the screen, and in the time the virtual car was off-road, as a percentage of the total game time (51.4 ± 15.7 and 50.2 ± 19.5, respectively). Conclusion: Adding vibrotactile feedback improved performance time during grasping in a dual-task paradigm. Prosthesis users may use vibrotactile feedback to perform better during daily tasks, when multiple cognitive demands are present.